2019
DOI: 10.1371/journal.ppat.1008110
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of transcription factor encoding gene StTCP23 by small RNAs derived from the virulence modulating region of potato spindle tuber viroid is associated with symptom development in potato

Abstract: Viroids are small, non-protein-coding RNAs which can induce disease symptoms in a variety of plant species. Potato (Solanum tuberosum L.) is the natural host of Potato spindle tuber viroid (PSTVd) where infection results in stunting, distortion of leaves and tubers and yield loss. Replication of PSTVd is accompanied by the accumulation of viroid-derived small RNAs (sRNAs) proposed to play a central role in disease symptom development. Here we report that PSTVd sRNAs direct RNA silencing in potato against StTCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 79 publications
(83 reference statements)
2
29
0
Order By: Relevance
“…Although RNA silencing has been experimentally shown to be involved in the pathogenesis of both chloroplastic [ 27 , 28 ] and nuclear [ 29 , 30 , 31 , 32 ] viroids, this mechanism does not appear responsible for the differences in pathogenicity of HSVd-h and HSVd-g54. This conclusion is based on the observation that none of the HSVd-sRNA species which differ in sequence between HSVd-g54 and HSVd-h were able to pair with any of the genes differentially expressed between HSVd-g54 and HSVd-h infected cucumber plants ( Tables S5 and S6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although RNA silencing has been experimentally shown to be involved in the pathogenesis of both chloroplastic [ 27 , 28 ] and nuclear [ 29 , 30 , 31 , 32 ] viroids, this mechanism does not appear responsible for the differences in pathogenicity of HSVd-h and HSVd-g54. This conclusion is based on the observation that none of the HSVd-sRNA species which differ in sequence between HSVd-g54 and HSVd-h were able to pair with any of the genes differentially expressed between HSVd-g54 and HSVd-h infected cucumber plants ( Tables S5 and S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a potato gene which encodes transcription factor StTCP23 was shown to be targeted by several sRNA species derived from the virulence-modulating region of PSTVd. The silencing of StTCP23 leads to the development of viroid-like symptoms in potato [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A vd-sRNA generated from the VMR of PSTVd was then shown to silence the callose synthase genes of tomato plants, and it was observed that suppression was more pronounced in plants infected with a severe strain than those infected with a mild strain [ 42 ]. More recently, vd-sRNAs derived from the VMR of PSTVd were reported to have silenced a transcription factor encoding gene StTCP23 in potato, leading to the development of disease symptoms [ 43 ]. Moreover, genes reported containing sequences that could be targeted by vd-sRNAs include tomato FRIGIDA- like protein 3 ( FRL3 ), chloride channel protein CLCb -like ( clcB ), ribosomal protein S3a - like ( RPS3A ), serine-threonine protein kinases , WD40-repeat protein ( WD40 ), and soluble inorganic pyrophosphatase of tobacco plants [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%